The impact of biomechanical analysis on sports performance of taekwondo athletes: a scoping review - Monterrosa Quintero, A.; Montenegro Ar-jona, O. A.; Poblete Valderrama, F. (Retos: nuevas tendencias en educación física, deporte y recreación, 2025)
Background: biomechanical analysis plays a fundamental role in enhancing athletic perfor-mance and preventing injuries, as it encompasses both qualitative and quantitative methods to evaluate techniques and tactics in taekwondo.Objective:this article aims to investigate recent technological advancements applied to taekwondo from a biomechanical perspective, focusing on kinematic and kinetic aspects based on studies published in the last five years.Methodology:A comprehensive review was conducted, analyzing biomechanical assessments that contribute to improving athletic performance through optimized techniques and tactics. Results:The findings highlight that variables such as arm swing speed and knee joint angle are crucial for effective jumping techniques. Moreover, the precise evaluation of strike force is es-sential for monitoring performance. Performance differences were also noted based on experi-ence, weight category, and gender. Elite athletes demonstrate greater impact forces and faster execution times, while medalists show superior reaction times, hip mobility, and favorable an-thropometric traits.Conclusions:The integration of biomechanical technologies in training enhances technical effi-cacy, supports injury prevention, and enables individualized strategies. These insights provide a robust foundation for future research and practical applications in taekwondo performance optimization.